A Systematic Review of Iranian Medicinal Plants Effective on Female Infertility - Mahnaz Yavangi (Journal of Global Pharma Technology, 2016)
Infertility is one of the common and rising problems of women. To treat female infertility, medicinal plants may be used in addition to chemical drugs and assisted reproductive technology. To conduct this review, the terms Fertility and Pregnancy in combination with Medicinal plants, Herb, and Phyto were used to search for and retrieve relevant publications indexed in international databases ISI and PubMed and domestic databases Iran Medex and ISC. The articles that fulfilled the inclusion criteria were analyzed. In this systematic review article, the medicinal plants that were found to be effective on female infertility indices were reported. These plants, according to this review article, are Nigella sativa, Panax ginseng, Phoenix dactylifera L., salep, Glycyrrhiza glabra, Apium graveolens L., and Foeniculum vulgare Mill. The medicinal plants used by Iranian people have been reported to exert optimal effects on female fertility in animal studies through antioxidant properties, increasing follicogenesis, hormonal compounds, and other effective compounds on hormonal system as well as enhancing sex cells viability. Keywords: Infertili1ty, Female, Medicinal plants, Iran.